1990
DOI: 10.2307/1130767
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hearing Impairment on the Quality of Attachment and Mother-Toddler Interaction

Abstract: In the present study, 41 hearing impaired and 41 hearing toddlers together with their hearing mothers were observed in Ainsworth's Strange Situation and during free play. Both security of attachment and ratings of maternal and toddler behavior during free play were remarkably similar for the hearing impaired and hearing dyads. In addition, security of attachment was related to the ratings of maternal and toddler behavior in a similar way for the hearing impaired and hearing toddlers. The results suggest that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 0 publications
3
45
0
3
Order By: Relevance
“…The mutual comprehension required between hearing mothers and deaf children for successful mother-child interactions decreases, with the result that deaf children do not comprehend their mothers' initiation acts and thus do not respond to them (Lederberg & Mobley, 1990;Meadow-Orlans & Steinberg, 1993). Further, hearing mothers of deaf children tend to be more controlling in their interactions than hearing mothers of hearing children (Lederberg & Mobley, 1990).…”
Section: Establishment Of Joint Attention In Dyads Involving Hearing mentioning
confidence: 99%
See 2 more Smart Citations
“…The mutual comprehension required between hearing mothers and deaf children for successful mother-child interactions decreases, with the result that deaf children do not comprehend their mothers' initiation acts and thus do not respond to them (Lederberg & Mobley, 1990;Meadow-Orlans & Steinberg, 1993). Further, hearing mothers of deaf children tend to be more controlling in their interactions than hearing mothers of hearing children (Lederberg & Mobley, 1990).…”
Section: Establishment Of Joint Attention In Dyads Involving Hearing mentioning
confidence: 99%
“…Ninety percent of these children are born to hearing parents who have little or no experience with hearing loss (Lederberg & Mobley, 1990). Because of the mismatched modes of communication between hearing mothers and deaf children and the lack of responsiveness of deaf children, these dyads often struggle to achieve the same levels of motherchild interactions as those experienced by hearing mother-hearing child dyads (Prezbindowski, Adamson, & Lederberg, 1998;Spencer, 2000;Spencer, Bodner-Johnson, & Gutfreund, 1992;Waxman, Spencer, & Poisson, 1996).…”
Section: Establishment Of Joint Attention In Dyads Involving Hearing mentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies of parents and their infants with disabilities reveal parent-child interaction that is characterized by infants being difficult to read (e.g., Field, 1980) and parents being insensitively directive (e.g., Hanzlik & Stevenson, 1986;Mahoney, Fors, & Wood, 1990), neither of which may bode well for the attachment relationship. Very few studies have examined the relationship between caregiver sensitivity and infant attachment security in dyads with infants with developmental delay, but the existing research suggests that the risk of insecure attachment for these children may be related to caregiver responsiveness (Lederberg & Mobley, 1990;Wasserman, Lennon, Allen, & Shilansky, 1987). In a longitudinal study of children with Down syndrome, Atkinson and his colleagues found that maternal coping style and affective distress interact to influence maternal sensitivity (Atkinson et al, 1995), and that maternal sensitivity and child cognitive level interact to predict attachment security (Atkinson et al 1999 (1995) found that the most effective were short-term behavioral approaches rather than longer-term, intensive psychotherapeutic approaches.…”
Section: The Importance Of Infant Attachment Securitymentioning
confidence: 99%
“…Some researchers have suggested that the attachment process and security of attachment is the same in children with delayed and typical developmental patterns (e.g., Speltz, Endriga, Fisher, & Mason, 1997). Other authors have indicated that a developmental delay interferes with interaction and proximity seeking between a mother and her infant and therefore the process of development of secure attachment is altered (Blacher & Meyers, 1983;Lederberg & Mobley, 1990;Vaughn & Bost, 1999). Some researchers have found a higher incidence of insecure attachment between mothers and their infants with chronic illness and/or developmental delays (e.g., Greenberg, Speltz, Deklyen, & Endriga, 1991;Mrazek, Casey, & Anderson, 1987;Speltz, Greenberg, & Deklyen, 1990), and others have suggested that a social-emotional delay, itself, may be the result of an insecure attachment (e.g., Sameroff & Emde, 1989).…”
Section: Introductionmentioning
confidence: 99%